The Identity of ‘Paran’ Vocabulary Character in The Kelabit Ethnic Custom Terms of Address - Mohammad Syawal Narawi, Nor Hasimah Ismail; Mardzelah Makhsin (International Journal of Advanced Science and Technology, 2020)
This Kelabit ethnic custom terms of address study is done based on the current scenario and practice problems custom terms of address based on Kelabit ethnic community. This studies purpose was aimed to explaining the selection vocabulary of the Paran custom terms of address as a symbol of Kelabit ethnic identity character. In addition, the study also stated about the concept and selection criteria custom terms of address. This study was conducted in Bintulu, Sarawak. Five ethnic Kelabit from Bario Highland and aged between 50 and 70 years of informant. The main data sources obtained through interview, observation, photography and analysis of documents. Study vocabulary name character is based on the theory of Paran presented by Lickona (1992). The study found that every individual to be granted the title of Paran is able to form a noble personality character and became a symbol of community identity Kelabit ethnic character. In addition, the title also to create individual identity in your welfare values for himself and for the ethnic Kelabit. In addition, there are 5 criteria have to be complied with by an individual in the granting of the title of the name of Paran in the ritual name change, i.e. gender, parenthood, family ancestry background, academic achievement and career.